Fabrication of Silver-doped Zinc Oxide Thin Films Through Optimized Sol-Gel Deposition and Nanoparticle Wetting Process - (:unkn) unknown (My University, 2018)
Zinc Oxide (ZnO) has been of significant interest as a Transparent Conductive Oxide (TCO) given its sizable direct band-gap, and as a potential substitute for Indium-Tin Oxide for use in opto-electronic and piezo-electric devices, due to its comparatively abundant and nontoxic precursor materials. Sol-gel processing is an easy, low-energy method for fabricating ZnO thin films, and there has been increasing interest in doping the compound such to give it p-type semiconductive character. This thesis thoroughly investigates sol-gel processing of ZnO thin solid films, with focus on wet-chemistry (sol-gel) methods of doping the material with silver (both as elemental ions and nanoparticles,) in the interest of achieving p-type doped ZnO. From dozens of similar but varying documented procedures, optimal processing methods and parameters for experimentation involving solutions-based doping were investigated and codified into a repeatable standard operating procedure (SOP), confirmed by X-Ray Diffraction results showing preferential (002)-peak, c-axis crystalline orientation. Heretofore unexplored study of the use of organic solvents as wetting agents and introduction of silver nanoparticles in layering processes within the sol-gel processing framework are shown to further improve c-axis orientation. A newly-adapted, quantified method of XRD preferential orientation analysis is implemented alongside UV-Visual bandgap analysis and SEM/AFM microscopy methods to further confirm improved crystallinity and reduced-diameter nanoscale c-axis oriented crystallites. These experiments and characterizations are analyzed in the context of structure and properties leading to material performance, with results documented in detailed appendices.
Keywords: p-type ZnO; Silver Doped; Silver Nanoparticle; Sol-gel; Thin Films; Zinc Oxide